Estimating fat-free mass in elite-level male rowers: a four-compartment model validation of laboratory and field methods - Kendall, K. L.; Fukuda, D. H.; Hyde, P. N.; Smith-Ryan, A. E.; MoonJ. R.; Stout, J. R. (Journal of Sports Sciences, 2017)
The purpose of this study was to investigate the accuracy of fat-free mass (FFM) estimates from two-compartment (2C) models including air displacement plethysmography (ADP), ultrasound (US), near-infrared interactance (NIR), and the Jackson and Pollock skinfold equation (SKF) against a criterion four-compartment (4C) model in elite male rowers. METHODS: Twenty-three elite-level male rowers (mean± SD; age 24.6 ± 2.2 years; stature: 191.4 ± 7.2 cm; mass: 87.2 ± 11.2 kg) participated in this investigation. All body composition assessments were performed on the same day in random order, except for hydrostatic weighing (HW), which was measured last. FFM was evaluated using a 4C model, which included total body water from bioimpedance spectroscopy, body volume from HW, and total body bone mineral via dual-energy X-ray absorptiometry. The major findings of the study were that the 2C models evaluated overestimated FFM and should be considered with caution for the assessment of FFM in elite male rowers. Future studies should use multiple-compartment models, with measurement of TBW and bone mineral content, for the estimation of FFM.